An unusual vertical swelling over the back - Vinod Kumar Viswanathan (Apollo Medicine, 2019)
Skeletal tuberculosis (TB) accounts for 1%–2% of all types of TB. The most common form of skeletal TB is Pott's disease, a disease of the spine; this entity comprises approximately half of skeletal TB cases. Tuberculous cold abscess can present as swelling on the back usually originating from the thoracic spine. Herewith is presented a rare case presentation of a patient who presented with a vertical swelling over the paraspinal region who on evaluation was found to have a cold abscess of tuberculous etiology arising from the ribs and tracking down the paraspinal region. This case is presented here for its rarity being a primary chest wall TB with no pulmonary involvement.